2021
DOI: 10.3389/fimmu.2021.674565
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Lymphoid Structures as a Predictive Biomarker of Response to Cancer Immunotherapies

Abstract: Tertiary lymphoid structures (TLS) are ectopic lymphoid formations which are formed under long-lasting inflammatory conditions, including tumours. TLS are composed predominantly of B cells, T cells and dendritic cells, and display various levels of organisation, from locally concentrated aggregates of immune cells, through clearly defined B cell follicles to mature follicles containing germinal centres. Their presence has been strongly associated with improved survival and clinical outcome upon cancer immunoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 64 publications
(105 reference statements)
0
35
0
Order By: Relevance
“…PDPN+ pCAFassigner subtype C CAFs have been shown to have an association with good prognosis and an immune-rich phenotype in human pancreatic cancers [35]. This is important because TLS content and activation status represent prognostic biomarkers for a good outcome and predictive biomarkers for response to immunotherapy in multiple tumour types, including PDAC [107][108][109][110][111][112][113][114]. In melanoma, PDPN+ CAF networks act as lymphoid organisers through production of TLS-promoting chemokines and through direct interaction with B cells, to orchestrate antitumour immunity [115,116].…”
Section: Are Icafs Desirable or Dangerous In Therapeutic Strategies?mentioning
confidence: 99%
“…PDPN+ pCAFassigner subtype C CAFs have been shown to have an association with good prognosis and an immune-rich phenotype in human pancreatic cancers [35]. This is important because TLS content and activation status represent prognostic biomarkers for a good outcome and predictive biomarkers for response to immunotherapy in multiple tumour types, including PDAC [107][108][109][110][111][112][113][114]. In melanoma, PDPN+ CAF networks act as lymphoid organisers through production of TLS-promoting chemokines and through direct interaction with B cells, to orchestrate antitumour immunity [115,116].…”
Section: Are Icafs Desirable or Dangerous In Therapeutic Strategies?mentioning
confidence: 99%
“…The potential of microbiome and its derived metabolome as biomarkers for predicting the efficacy of immunotherapy has been validated in melanoma ( 58 ), lung cancer ( 59 ), hepatobiliary cancer ( 60 ), and colorectal cancer ( 61 ). Several studies have demonstrated that clinical outcomes of immunotherapy for solid tumors are strongly correlated with the presence of TLSs, suggesting that TLSs may be a valid predictive indicator in the future ( 62 ). Elevated levels of carcinoembryonic antigen (CEA) have also been reported to negatively correlate with the prognosis of resected NSCLC patients receiving ICB therapy ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that an orchestrated immune response to cancer is elicited locally in TLS, which resemble the structures of secondary lymphoid organs [ 14 ]. TLS predominantly consists of B cells and T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Neither FDCs nor GCs is found in immature TLS [ 15 , 16 ]. Together with T and B cells, DCs, neutrophils, macrophages, HEVs, CD4+ T follicular helper cells (T FH ), CD8+ cytotoxic T cells, CD4+ regulatory T cells (T Reg ), and innate lymphoid cells can be detected in TLS [ 14 ]. Several gene signatures have been used to detect TLSs in the transcriptomic analyses of human cancers, which include 12 chemokine signatures, T FH cell signatures, T H 1 and B cell signatures, and plasma cell signatures [ 6 ].…”
Section: Discussionmentioning
confidence: 99%